Sunday

April 20, 2014

April 20, 2014

Posted by **Amy** on Sunday, April 10, 2011 at 2:54pm.

0=-2(8t^2-32t+21)

- Algebra -
**PsyDAG**, Monday, April 11, 2011 at 2:30pm-16t^2 + 64t - 42 = 0

Divide end values into two factors (-7,6 or 7,-6, or 21,-2 or -21,2 or 14, -3 or so on) (16,-1 or -16,1 or 4,-4 or -8, 2 and so on) to see how their sum will get the center value.

From there it is trial and error. Start trying.

**Related Questions**

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

pre algebra - solve the equation step by step.list each step along with the ...

algebra 1 - ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multi-...

algerbra - solve the equation step by step list each step along with the ...

Math - Step 1 = 3 boxes Step 2 = 6 boxes Step 3 = 11 boxes Step 4 = 18 boxes How...

ALGEBRA HELP - When solving the equation, what property was used to go from step...

Algebra 1 - -3x + 6 < 21 I need help in solving this problem step by step. ...

Algebra 1 - f(x)=x^2+3 Solve for f(2)and f(-5) I need help, can someone please ...

Algebra 1 - f(x)=x^2+3 Solve for f(2)and f(-5) I need help, can someone please ...

precal - 4=2cos(pi/6t-2pi/3)+4 How do i solve this step by step ith ...